Bacillus pumilus Septic Arthritis in a Healthy Child. (24th April 2016) - Shivamurthy, V. M.; Gantt, Soren; Reilly, Christopher; Tilley, Peter; Guzman, Jaime; Tucker, Lori
Abstract : We report a case of septic arthritis caused by a Bacillus species, B. pumilus, occurring in a healthy child. This organism rarely causes serious infections and has only been described in newborns and immunocompromised individuals or as a skin infection. This child developed an indolent joint swelling after a minor skin injury, and symptoms were initially thought most consistent with chronic arthritis. The case demonstrates that clinicians should consider joint infection in children presenting with acute monoarticular swelling, even without prominent systemic features.